Trends in tropical tree growth: re‐analyses confirm earlier findings. (17th February 2017) - van der Sleen, Peter; Groenendijk, Peter; Vlam, Mart; Anten, Niels P. R.; Bongers, Frans; Zuidema, Pieter A.
Abstract : In a recent Opinion article, Brienen et al . (2016) raise doubts about our finding that tropical tree growth has not increased during 150 years of CO2 rise (Groenendijk et al ., 2015; van der Sleen et al ., 2015). They claim that our tree‐ring data contain evidence for historical growth stimulation that was concealed due to failing regeneration in several species. Here we show that (i) the correction method proposed by Brienen et al . induces a bias towards finding positive growth trends, (ii) the results of Brienen et al . rest on selective removal of species, (iii) there is a simple and effective way to accommodate effects of recruitment failure by subsetting data, and (iv) the application of this method confirms our earlier findings. Thus, our results are robust to effects of recruitment failure and our conclusions remain unchanged: we find no evidence for historical growth changes in our studied tree species.